The rs2046210 Polymorphism Is Associated with Endometriosis Risk and Elevated Estrogen Receptor 1 Expression in the Eutopic Endometrium of Women with the Disease - Proestling, Katharina; Schreiber, Martin; Miedl, Heidi; Hudson, Quanah J.; Husslein, Heinrich; Kuessel, Lorenz; Gstoettner, Manuela; Wenzl, Rene; Yotova, Iveta (Biomedicines, 2024)
In this focused genetic case–control study, we analyzed two functional single-nucleotide variants (SNVs) associated with breast cancer risk (rs2046210, rs9383590) and one risk SNV for an implantation defect and infertility (rs9340799) for their association with endometriosis susceptibility, progression and ESR1 gene regulation in endometriosis patients. The rs2046210, rs9383590 and rs9340799 SNVs were genotyped in 153 endometriosis patients and 87 control subjects with Caucasian ancestry. We analyzed the association of all SNVs with endometriosis susceptibility in all patients and in subgroups and assessed the concordance between the SNVs. Quantitative reverse transcription PCR was used to determine ESR1 gene expression in the eutopic endometrial tissue of the controls and endometriosis patients. The heterozygous rs2046210 GA genotype was associated with significantly increased endometriosis risk, particularly in younger, leaner and infertile women and with an increased ESR1 gene expression in the eutopic endometrium of these patients, compared to controls. The minor AA genotype of rs2046210 was identified as a potential risk factor for endometriosis progression in women with mild endometriosis. The results from this analysis indicate that rs2046210 may be a functional genetic variant associated with endometriosis development and progression.